Event-based entrepreneurship - Fisher, Greg; Josefy, Matthew A.; Neubert, Emily (Journal of Business Venturing, 2024)
Many entrepreneurial opportunities are associated with events, including sports competitions, races and tournaments, concerts and music festivals, and conferences and exhibitions, yet this variant of entrepreneurship has not been specifically accounted for in the literature. We integrate insights from entrepreneurship research with research on temporary organizational forms, stakeholder theory, and platform strategy to define Event-Based Entrepreneurship (EBE) and propose factors that account for the founding and scaling of event-based ventures. In so doing, we lay the conceptual foundations and offer theoretical and practical directions for an expanded research agenda on EBE.